Dramatherapy and Psychodrama with Looked-After Children and Young People. Issue 2 (November 2017) - Moore, Joan; Andersen-Warren, Madeline; Kirk, Kate
This paper provides the results of a questionnaire constructed to solicit information about the creative structures that dramatherapists and psychodramatists are using in therapy with Looked-After children (LAC) and young people. After a brief account of the research itself the results are presented; this starts by defining the assessment and evaluation tools that are used by the practitioners. The particular needs of this client group are examined and what follows is the analysis and explanation of the creative ways in which the practitioners meet the needs of LAC and young people.